2021
DOI: 10.1016/j.jbc.2021.100523
|View full text |Cite
|
Sign up to set email alerts
|

Effective delivery of STING agonist using exosomes suppresses tumor growth and enhances antitumor immunity

Abstract: The Stimulator of Interferon Genes (STING) pathway is implicated in the innate immune response and is important in both oncogenesis and cancer treatment. Specifically, activation of the cytosolic DNA sensor STING in antigen-presenting cells (APCs) induces a type I interferon response and cytokine production that facilitates antitumor immune therapy. However, use of STING agonists (STINGa) as a cancer therapeutic has been limited by unfavorable pharmacological properties and targeting inefficiency due to rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Importantly, evACE2 possesses an 80-fold better efficiency to block SARS-CoV-2 infection than soluble rhACE2. Of note, it has been recently reported that the exosomal delivery of STINGa potentiates its uptake into dendritic cells compared with STINGa alone, which led to increased accumulation of activated CD8 + T-cells and an antitumor immune response 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, evACE2 possesses an 80-fold better efficiency to block SARS-CoV-2 infection than soluble rhACE2. Of note, it has been recently reported that the exosomal delivery of STINGa potentiates its uptake into dendritic cells compared with STINGa alone, which led to increased accumulation of activated CD8 + T-cells and an antitumor immune response 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic nanoparticles assembled in the presence of CDNs have been shown to enhance cytosolic delivery and activate STING-dependent anti-tumor responses (Lu et al, 2020;Wilson et al, 2018). Exosomes loaded with CDNs appear to achieve similar enhancements (Jang et al, 2021;McAndrews et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…McAndrews et al used exosomes loaded with STING’s GMP-AMP cyclic agonist (iExoSTINGa) to specifically target the STING pathway in APCs with greater efficacy than STINGa alone in inhibiting B16F10 cancer proliferation. Furthermore, iExoSTINGa showed greater uptake of STINGa in dendritic cells than STINGa alone, with a significant increase in stimulated CD8 + T cells and an improved antitumor immune response [ 113 ].…”
Section: Exosomes and Breast Cancermentioning
confidence: 99%